Challenges in managing difficult‐to‐treat asthma in children: Stop, look, and listen. Issue 3 (11th November 2019) - Hoch, Heather; Kattan, Meyer; Szefler, Stanley J.
Abstract: It is recognized that asthma places a significant economic burden on the United States, with a total cost of 81.9 billion total costs including costs incurred by absenteeism and mortality. Severe asthma places a large burden of morbidity on children and their caregivers, including severe exacerbations, medication side effects, increased missed school days leading to impaired school performance, and lower caregiver quality of life. Therefore, we need to take a careful look at how we can make asthma care more efficient and cost effective, especially for those children with severe asthma. The 2019 American Thoracic Society symposium reported in this theme issue presented four aspects of managing severe asthma in children that merit attention including patient variables that affect severe asthma, understanding patient behaviors around medications, the appropriate use of bronchoscopy in diagnosis and management of severe asthma, and also the rational use of biologic therapy. This editorial will summarize key points in each of these reviews and prompt a more careful reading of each contribution.